PENGARUH UKURAN PERUSAHAAN, INTENSITAS ASET TETAP, DAN TINGKAT UTANG TERHADAP MANAJEMEN PAJAK - Yudawirawan, Moh. Yuddy (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to analyze and provide empirical evidence on the influence of firm size, fixed asset intensity, and leverage on tax management. This study adopts an associative quantitative approach using secondary data from the financial reports of consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The sample selection procedure utilizes purposive sampling method, resulting in a sample of 25 companies that meet the criteria. The variables used in this research include firm size (X1) as the first independent variable, fixed asset intensity (X2) as the second independent variable, leverage (X3) as the third independent variable, and tax management (Y) as the dependent variable. The analytical technique employed is panel data regression analysis using E-views 12 software. The research findings reveal that the size of a firm plays a crucial role in shaping its tax management practices, whereas factors such as fixed asset intensity and leverage do not have a significant impact on how taxes are managed. This suggests that larger firms may have more resources or capabilities to handle tax-related strategies effectively, while the composition of assets or the extent of borrowing does not substantially alter their approach to tax management.